"Puffin love": Performing and creating Arctic landscapes in Iceland through souvenirs. (June 2018) - Lund, Katrín Anna; Kjartansdóttir, Katla; Loftsdóttir, Kristín
This article looks at the creation of Iceland's capital, Reykjavík, as an Arctic tourism destination with a focus on souvenir production and consumption. We regard souvenirs to be particularly interesting for investigating the creation and materialization of the Arctic, in the light of how landscapes, in our case the urban landscape of Reykjavík, are constantly performed and narrated through objects. A special attention is given to the Atlantic Puffin that in recent years has become the Icelandic souvenir sine qua non and a veritable symbol for souvenir consumption in Iceland. We explore the urban landscapes of downtown Reykjavík with a focus on puffins in order to introduce the city's tensioned landscapes, especially regarding the complex material composition and meanings of the Atlantic Puffin in order to gain an understanding of its role in shaping the Arctic landscapes of Reykjavík.